Past and Future of Non-Saccharomyces Yeasts: From Spoilage Microorganisms to Biotechnological Tools for Improving Wine Aroma Complexity - Padilla, Beatriz; Gil, José V.; Manzanares, Paloma (Frontiers in Microbiology, 2016)
It is well established that non-Saccharomyces wine yeasts, considered in the past as undesired or spoilage yeasts, can enhance the analytical composition and aroma profile of the wine. The contribution of non-Saccharomyces yeasts, including the ability to secret enzymes and produce secondary metabolites, glycerol and ethanol, release of mannoproteins or contributions to color stability, is species- and strain-specific, pointing out the key importance of a clever strain selection. The use of mixed starters of selected non-Saccharomyces yeasts with strains of Saccharomyces cerevisiae represents an alternative to both spontaneous and inoculated wine fermentations, taking advantage of the potential positive role that non-Saccharomyces wine yeast species play in the organoleptic characteristics of wine. In this context mixed starters can meet the growing demand for new and improved wine yeast strains adapted to different types and styles of wine. With the aim of presenting old and new evidences on the potential of non-Saccharomyces yeasts to address this market trend, we mainly review the studies focused on non-Saccharomyces strain selection and design of mixed starters directed to improve primary and secondary aroma of wines. The ability of non-Saccharomyces wine yeasts to produce enzymes and metabolites of oenological relevance is also discussed.